Voices Welcomes Interviews - Stachyra, Krystof (Voices: A World Forum for Music Therapy, 2010)
We've decided to focus the November 1st issue of Voices on Helen Bonny’s life, work and music therapy method. We look for people who met her, knew her and whose professional life has been influenced by Helen Bonny.